2019
DOI: 10.1097/dss.0000000000001724
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, Progression, and Treatment of Endovenous Heat-Induced Thrombosis Class 2 or Greater After Endovenous Radiofrequency Ablation

Abstract: BACKGROUND Endovenous heat-induced thrombosis (EHIT) is a thrombus that extends from an ablated saphenous vein into the common femoral vein after endovenous radiofrequency ablation (RFA). OBJECTIVE To investigate the incidence, progression, treatment, and risk factors associated with EHIT-2 or greater after RFA. MATERIALS AND METHODS This retrospective study included patients diagnosed with symptomatic super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It was reported that a >6 mm GSV proximal diameter was an independent risk factor for endovenous laser recurrence and foam sclerotherapy after varicose veins of lower extremities. However, the recurrence incidence and venous thrombosis increased after radiofrequency ablation when the GSV proximal diameter was >8 mm [ 18 ]. Therefore, the definition of GSV proximal diameter was set as >8 mm in this study [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a >6 mm GSV proximal diameter was an independent risk factor for endovenous laser recurrence and foam sclerotherapy after varicose veins of lower extremities. However, the recurrence incidence and venous thrombosis increased after radiofrequency ablation when the GSV proximal diameter was >8 mm [ 18 ]. Therefore, the definition of GSV proximal diameter was set as >8 mm in this study [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…CRP has half life of 19 hours and gets peak level at 36-50 hours [42], whereas IL-6 has half life of 2-3 hours and gets peak level at 12-18 hours [43]. Because half life of CRP is longer than IL-6, 24-hr postoperative level of CRP increased less than IL-6.…”
Section: Ev-rfa Venous Stripping P-valuementioning
confidence: 99%
“…With class I, both subgroups require no treatment and no further surveillance ultrasound scans are required unless to evaluate for research purposes. In a small proportion of patients with class II EHIT and above, small cohort studies have suggested that EHIT can progress to higher classes, 3 , 5 and therefore, surveillance is required, and treatment may be indicated. In class II, patients may be stratified into low and high risk for thrombus propagation.…”
Section: Management Recommendationsmentioning
confidence: 99%